Removal of PFAS by Biological Methods - Karimi Douna, Bahareh; Yousefi, Hossein (Asian Pacific Journal of Environment and Cancer, 2023)
The ubiquitous presence of poly- and perfluoroalkyl (PFAS) is a severe concern in view of their bioaccumulation and persistence in the environment. Subsequently, through feeding or drinking contaminated water, this contaminant will enter the body of living organisms and humans and will cause serious diseases, specifically, different types of cancers. There are many chemical, physical and biological methods used for PFAS removal. However, besides some limitations, biological methods are one of the most cost-effective, eco-friendly, and simplest in operation process. Biological techniques include bioremediation, phytoremediation, vermiremediation, biodegradation, and bioadsorption, comprehensively reviewed in this study. Since combination of different techniques are more effective and efficient than a single method, we also reviewed different kinds of combination methods.